Optimalisasi Minat dan Motivasi Belajar Bahasa Arab di Madin Miftahul Ulum Kesugihan, Pulung, Ponorogo - Widya Nafiatus Sholikhah; Diyan Putri Ayu (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Learning Arabic is often associated with learning Islam. However, in educational institutions there are often obstacles in motivating students to focus on learning Arabic. This study aims to determine the optimization of students' motivation and interest in learning Arabic. This type of research is qualitative with a qualitative descriptive approach. The service method used is community Based Research (CBR) where this method teaches researchers so that from the beginning of service has involved the community. Data sources are obtained through observation and documentation based on primary and secondary sources. The results of research and conclusions from this article are for optimizing students' Arabic learning inseparable from students' motivation and interest in learning and the methods applied by teachers in learning.